A Structural Health Monitoring (SHM) of composite patch repair for aircraft part and structures using principal component analysis - Mohd Aris, Khairul Dahri (2015)
The use of advanced composite structures on aircraft is increasing. New aircraft, such as the Airbus A350 and the Boeing B787, have more than 50% of their structure originating from composite materials especially carbon fiber reinforced plastic (CFRP). Delamination, disbonding, voids and barely visible internal damage (BVID) are some of the damages uniquely found in the composite structure. Once the repair is carried out, the structural health monitoring (SHM) has the ability to detect structural anomalies where human dependency can be minimized. However, most SHM works are concentrating on pristine structure on repaired structure. Therefore the behaviour of SHM at undamaged, damaged and repaired conditions on carbon fiber reinforced plastic (CFRP) are being investigated in this research.. The motivation of the research is to optimize the structural health monitoring (SHM) in comparing the structural response undamaged, damaged and repaired of CFRP structures by using Principal Component Analysis (PCA) through Amplitude Based Assessment (ABA) and Conditional Structural Index (CSI). The objectives of the research are to undertake a feasibility study on Lamb wave propagation over undamaged, damaged and repaired composite panels via smart PZT sensor by using PCA to evaluate the structural conditions of CFRP panels. PZT sensors are used to interrogate and retrieve the surface wave across the investigated structures via online and offline on the undamaged damaged and repaired structures of similar origin. Result shows that although the structural integrity has returned back to its pristine condition, the repaired structure response is diverging from the undamaged conditions. The novelty in this research is the comparative results between undamaged, damaged and repaired response of an aircraft structures originated from CFRP panels which will assist in interpreting the structural health status at maintenance level.